Pelatihan Test of English Foreign Language (TOEFL) dan Try-Out Pada Mahasiswa APOTEKER - Muliaty Ibrahim; Sukmawati; Suciati (ABDI SAMULANG: Jurnal Pengabdian Kepada Masyarakat, 2023)
Test of English Foreign Language (TOEFL) and Try-out training is one of Megarezky University's programs as a requirement for student graduation for the final completion of studies that must meet the graduation standards of Megarezky University students, requirements for continuing to a higher level of education, work entry requirements and even used in promotion. The target in this Community Service activity is students of the PHARMACIST Study Program, Faculty of Pharmacy, Megarezky University with a total of 9 students. This activity lasted for nine hours. The implementation of this training uses methods, lectures, try-outs, and audio-visuals.In the lecture method, the PKM team explained the theory of how to answer TOEFL questions in Listening, Structure, and Reading activities. The Try-out method of doing the TOEFL TEST is related to the material that has been presented in the training activities. The results of the try out can be seen the score score of the PHARMACIST students of Megarezky University directly, then return to provide a discussion of the test questions on each skill. This training provides an overview to UNIMERZ PHARMACIST students when completing the TOEFL test. So they can pass with a TOEFL score that matches the standard.